Sinteza stranskoverižnih tekočekristaliničnih poliuretanov z elektrostatskimi interakcijami - Mirčeva, Aneta (Kovine zlitine tehnologije, 1999)
Novel supramolecular side-chain liquide crystalline polyurethanes were prepared on the basis of electrostatic interactions between carboxylated polyurethane and aminated biphenyl mesogenic compounds (1,1,1-triethyl-(4-(4'-metoxybifenyl)oxy)alkyl amino bromides). By elimination of HBr, the ionic segments that interacts electrostatically (-?$COO^-$? of the polymer backbone and quaternary nitrogen of the mesogenic unit) are formed. The obtained polymeric liquid crystalline ionic complexes have smectic type of mesophase and show a tendency toward crystallization.
Keywords: poliuretani; kristaliničnost; sinteza; analiza